Deformation of µm- and mm-sized Fe2.4wt%Si single- and bi-crystals with a high angle grain boundary at room temperature. (1st August 2020) - Heller, M.; Gibson, J.S.K.-L.; Pei, R.; Korte-Kerzel, S.
Abstract: Plasticity in body-centred cubic (BCC) metals, including dislocation interactions at grain boundaries, is much less understood than in face-centred cubic (FCC) metals. At low temperatures additional resistance to dislocation motion due to the Peierls barrier becomes important, which increases the complexity of plasticity. Iron-silicon steel is an interesting, model BCC material since the evolution of the dislocation structure in specifically-oriented grains and at particular grain boundaries have far-reaching effects not only on the deformation behaviour but also on the magnetic properties, which are important in its final application as electrical steel. In this study, two different orientations of micropillars (1, 2, 4 µm in diameter) and macropillars (2500 µm) and their corresponding bi-crystals are analysed after compression experiments with respect to the effect of size on strength and dislocation structures. Using different experimental methods, such as slip trace analysis, plane tilt analysis and cross-sectional EBSD, we show that direct slip transmission occurs, and different slip systems are active in the bi-crystals compared to their single-crystal counterparts. However, in spite of direct transmission and a very high transmission factor, dislocation pile-up at the grain boundary is also observed at early stages of deformation. Moreover, an effect of size scaling with the pillar size in single-crystals and the grain size in bi-crystals is found, which is consistent with investigations elsewhere in FCC metals. Graphical abstract: Image, graphical abstract